2021
DOI: 10.1021/acs.jnatprod.0c00975
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV Improves Tibial Defect in Rats and Promotes Proliferation and Osteogenic Differentiation of hBMSCs through MiR-124-3p.1/STAT3 Axis

Abstract: Astragaloside IV (AST-IV) facilitates the proliferation and migration of osteoblastlike cells. We sought to explore the effect and potential mechanism of AST-IV on regeneration of tibial defects. To reveal the effect of AST-IV on regeneration of tibial defects in rat, HE staining and microcomputed tomography (μCT) were performed on tibial bone. The binding relationship between miR-124-3p.1 and STAT3 was analyzed by TargetScan V7.2 and a dual-luciferase reporter assay. Human bone marrow mesenchymal stromal/stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Previous studies have demonstrated that miRNAs act as important regulators for the stemness of oral mesenchymal stem cells [37,38]. Recently, the critical role of miR-124-3p.1 in osteogenic differentiation of human BMSCs has been previously demonstrated [34]. We, therefore, assume that miR-124-3p.1 can inhibit osteogenic and odontogenic differentiation of SCAPs through the MACF1/smad7 axis.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Previous studies have demonstrated that miRNAs act as important regulators for the stemness of oral mesenchymal stem cells [37,38]. Recently, the critical role of miR-124-3p.1 in osteogenic differentiation of human BMSCs has been previously demonstrated [34]. We, therefore, assume that miR-124-3p.1 can inhibit osteogenic and odontogenic differentiation of SCAPs through the MACF1/smad7 axis.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, miR-124-3p.1 sensitizes carboplatin induced mitochondrial apoptosis by inhibiting CAV1 in ovarian cancer [33]. Recently, there are studies demonstrated that miR-124-3p.1 overexpression negatively regulated proliferation and osteogenic differentiation of human bone marrow mesenchymal stem cells (BMSCs) [34]. However, the role of miR-124-3p.1 in the differentiation of SCAPs are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Bone marrow mesenchymal stem cells, the important component, and regulator of the bone marrow microenvironment have the role of supporting hematopoiesis [ 28 ]. It has been reported that astragaloside A can promote the proliferation and osteogenic differentiation of bone marrow mesenchymal stem cells [ 29 ], and ferulic acid also has the same effect [ 30 ]. Furthermore, some scholars have shown that ferulic acid, calycosin, and astragaloside A can be used alone or in combination to increase the content of RBC, WBC, and HGB [ 31 ], which was supported by our peripheral blood tests.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that miR-296-5p also directly targeted STAT3 in colorectal cancer and non-small cell lung cancer [ 25 , 26 ]. STAT3 has been reported to promote proliferation and osteogenic differentiation of hBMSCs [ 27 ]. Consistent with our results, STAT3 was also found to promote cell proliferation and differentiation and restrains apoptosis in Dex-treated hBMSCs.…”
Section: Discussionmentioning
confidence: 99%